The role of phosphoinositide 3-kinase and phosphatidic acid in the regulation of mammalian target of rapamycin following eccentric contractions - O’Neil, T K (Blackwell Science Inc, 2009)
Resistance exercise induces a hypertrophic response in skeletal muscle and recent studies have begun to shed light on the molecular mechanisms involved in this process. For example, several studies indicate that signalling by the mammalian target of rapamycin (mTOR) is necessary for a hypertrophic response. Furthermore, resistance exercise has been proposed to activate mTOR signalling through an upstream pathway involving the phosphoinositide 3-kinase (PI3K) and protein kinase B (PKB); however, this hypothesis has not been thoroughly tested. To test this hypothesis, we first evaluated the temporal pattern of signalling through PI3K–PKB and mTOR following a bout of resistance exercise with eccentric contractions (EC). Our results indicated that the activation of signalling through PI3K–PKB is a transient event (<15 min), while the activation of mTOR is sustained for a long duration (>12 h). Furthermore, inhibition of PI3K–PKB activity did not prevent the activation of mTOR signalling by ECs, indicating that PI3K–PKB is not part of the upstream regulatory pathway. These observations led us to investigate an alternative pathway for the activation of mTOR signalling involving the synthesis of phosphatidic acid (PA) by phospholipase D (PLD). Our results demonstrate that ECs induce a sustained elevation in [PA] and inhibiting the synthesis of PA by PLD prevented the activation of mTOR. Furthermore, we determined that similar to ECs, PA activates mTOR signalling through a PI3K–PKB-independent mechanism. Combined, the results of this study indicate that the activation of mTOR following eccentric contractions occurs through a PI3K–PKB-independent mechanism that requires PLD and PA.